PENGEMBANGAN MEDIA PUZZLE MUFRODAT UNTUK MENINGKATKAN PENGUASAAN KOSAKATA SISWA DI KELAS III MI MUJAHIDIN NW JEMPONG - Handayani, Safitri; Ramli; Sani, Muhammad Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low mastery of Arabic vocabulary among students and the lack of variation in the use of learning media in grade III students of MI Nahdatul Mujahidin NW Jempong. This study aims to determine the feasibility and effectiveness of the mufrodat puzzle media in improving students' mastery of Arabic vocabulary. This study uses the Research and Development (R&D) method with a 4D development model that includes the Define, Design, Develop, and Disseminate stages. Data collection techniques are carried out through questionnaires, observations, interviews, tests and performance assessments. The research instruments are validation sheets from media experts and material experts, test questions and performance assessment rubrics. Data are analyzed qualitatively and quantitatively. The results of the study indicate that the mufrodat puzzle media is declared very suitable for use based on media expert validation with a percentage of 92.5% and material expert validation of 100%. The results of the N-Gain calculation obtained a value of 0.60 with a moderate category and an interpretation of quite effective, which indicates an increase in students' vocabulary mastery after using the media. In addition, the results of the performance assessment also show that students achieve good achievements in the aspect of vocabulary mastery. Thus, vocabulary puzzle media can be an alternative for teachers in improving students' vocabulary mastery while making learning more interesting and in accordance with the characteristics of grade III students.